(untitled) (Jurnal Bina Praja, 2025)
The Indonesian government has initiated the implementation of Digital ID or Digital Population Identity (IKD) as part of the national digital transformation strategy, particularly in supporting the Electronic-Based Government System (SPBE) and the integration of public services. However, IKD adoption remains relatively low. This is indicated by the high demand for e-KTP forms over the past 5 years, especially since the IKD was implemented in 2022. Based on these conditions, this study asks three main questions: (1) What are the strengths and strategic opportunities that support the implementation of IKD? (2) What are the real results and public aspirations regarding the implementation of IKD? and (3) How can IKD support digital transformation in Indonesia? This study employed an explanatory sequential mixed-methods approach. The quantitative phase was conducted first through a survey of 688 respondents who assessed eight policy alternatives based on effectiveness, efficiency, and impact. A thematic analysis of open-ended responses in the same questionnaire followed the qualitative phase. All data were then analyzed using the SOAR (Strengths, Opportunities, Aspirations, Results) framework to map policy strategies based on strengths, opportunities, public expectations, and expected outcomes. The research results showed that the main strength lies in a centralized population data infrastructure and continuously evolving regulations. Strategic opportunities include the integration of IKD into the Priority Population Data Service (SPBE) through GovTech INA Digital, as well as the utilization of digital data verification in the financial and banking sectors. Public aspirations are reflected in the need for digital literacy and better personal data protection, while expected outcomes, such as optimizing IKD-based public services, have not been fully achieved. Meanwhile, IKD has not been fully able to support the digital transformation process in Indonesia. This study concludes that digital information technology (IKD) policy strategies need to be directed at integrating IKD with public services, strengthening cross-sector collaboration, developing responsive regulations, and conducting massive and inclusive public education. These findings contribute to the formulation of service-oriented, evidence-based, and sustainable digital transformation policies to support digital transformation in Indonesia.